Improved performance of electroplated grinding wheels using a new method of controlled grain size sorting. (December 2017) - Lyu, Yushan; Yu, Haiyue; Wang, Jun; Zhao, Guowei; Liu, Zhizhen
Abstract: The protrusion heights of grains on electroplated grinding wheel are uneven. This phenomenon has a negative influence on the grinding performance of electroplated grinding wheel. In this paper, CBN and diamond grains were sorted by hydraulic power method. Four kinds of electroplated grinding wheels were fabricated with selected and unselected CBN diamond grains. Then, the surface roughness of workpieces ground by the four kinds of grinding wheels were investigated and analyzed in contrast experiments. The experimental results show that the grains sorting method using hydraulic power can homogenize the size of grains; and lower ground surface roughness has been obtained by the electroplated grinding wheels with the help of the new method of controlled grain size sorting.